Budidaya Terung Ungu di Pekarangan di Desa Ciawijapura Kecamatan Susukan Lebak Kabupaten Cirebon - Umi Trisnaningsih; Siti Wahyuni; Wachdijono Wachdijono (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2021)
Yard land can be used as a family food barn. One of the efforts to overcome the limitations of land is by cultivating in a limited place (bag culture system) such as polybags, pots or used buckets. In Ciawijapura Village, Susukan Lebak Sub-district, Cirebon Regency, purple eggplant is commonly cultivated in dry land, as well as in yards. This Community Service Program (Pengabdian Kepada Masyarakat/PKM) is aimed at increasing the knowledge of Family Welfare Building Motivation Team (Tim Penggerak Pembinaan Kesejahteraan Keluarga/TP-PKK) cadres and members of Farmer Women Group (Kelompok Wanita Tani/KWT) Al Istiqomah about cultivating purple eggplant in a bag culture system. The methods used are training and mentoring. The evaluation results showed that there was a significant increase in knowledge between before and after the training, that is, from 73% to 89% of the total expected value. The participants were able to understand the difference between cultivating purple eggplant on land and in a bag culture system.